PEMBERDAYAAN MASYARAKAT BIDANG KEAGAMAAN ISLAM DI KELURAHAN TIHU, KECAMATAN TELUK AMBON, PROVINSI MALUKU - Rizki Muhammad Ramdhan; Afdhal Afdhal; Asep Asep (Universitas Pattimura, 2023)
The Community empowerment is an effort to provide strength and capability to the community to become self-sufficient and develop their potential. It is an effort to help the community improve their quality of life, whether in terms of religion, economy, or social aspects. One way of serving the community is through empowering them with Islamic religious activities. Community empowerment through Islamic religion in the Tihu Village, Teluk Ambon District, Maluku Province aims to increase religious awareness, strengthen religious values, develop skills, increase tolerance, and improve the welfare of the community. This community service activity is carried out by providing understanding and experience of Islamic religion that aligns with the values of goodness and truth. Community empowerment through Islamic religious activities is carried out through preaching, guidance, or religious counseling. Through these activities, 70% of the participants already understand and can implement worship activities, especially in anticipation of the holy month of Ramadan. Therefore, community empowerment through Islamic religious activities needs to be continually encouraged and developed in building a peaceful and prosperous community harmony.